Self-similar length-displacement scaling achieved by scale-dependent growth processes: Evidence from the Atacama Fault System. (April 2020) - Stanton-Yonge, A.; Cembrano, J.; Griffith, W.A.; Jensen, E.; Mitchell, T.M.
Abstract: The complex process of tip-propagation and growth of natural faults remains poorly understood. We analyse field structural data of strike-slip faults from the Atacama Fault System using fracture mechanics theory to depict the mechanical controls of fault growth in crystalline rocks. We calculate the displacement-length relationship of faults developed in the same rock type and tectonic regime, covering a range of five orders of magnitude, showing a linear scaling defined by d max = 0.0337 L 1.02 . A multiple linear regression approach based on the cohesive end zone (CEZ) crack model was formulated to estimate the range of possible effective elastic moduli, cohesive endzone lengths, stress drops, and fracture energies from displacement distributions mapped on natural faults. Our results challenge the existent paradigm wherein the self-similarity of fault growth is only achieved under the condition of invariable stresses and elastic properties. We propose a model of self-similar fault growth with scale-dependent evolution of shear modulus, cohesive end zone length and stress drop. These results also have implications for determination of stress drop for small earthquakes that are consistent with recent advances in observational seismology. Highlights: We find a linear displacement to length relationship for faults in crystalline rocks. We use a CEZ crack model to invert for tractions from mapped fault slip distributions. We propose a model of self-similar fault growth. Fault growth is enabled by scale-dependent evolution of key mechanical parameters.